1998
DOI: 10.1523/jneurosci.18-07-02729.1998
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Noradrenaline–Dopamine Coupling in the Locomotor Activating Effects of d-Amphetamine

Abstract: The locomotor hyperactivity induced by systemic or local (nucleus accumbens) D-amphetamine injections can be blocked by systemic or local (prefrontal cortex) injections of prazosin, an alpha1-adrenergic antagonist (Blance et al., 1994). Microdialysis studies performed on freely moving animals indicated that prazosin (0.5 mg/kg, i.p.) does not modify the increase in the extracellular dopamine (DA) levels in the nucleus accumbens that are induced by D-amphetamine (2.0 mg/kg, i.p.), but it inhibits the D-amphetam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
222
1
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(244 citation statements)
references
References 42 publications
18
222
1
3
Order By: Relevance
“…The effect of prazosin observed here is similar to the effects reported in other studies examining the role of the α 1 -adrenergic receptor in the locomotor response to amphetamine or cocaine (Arnt 1995;Blanc et al 1994;Darracq et al 1998;Dickinson et al 1988;Drouin et al 2002a;Drouin et al 2002b;Snoddy et al 1985;Wellman et al 2002). In fact, our data indicate that MDMA-induced motor behavior is more sensitive to α 1 -adrenoceptor blockade than that produced by (+)-amphetamine.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The effect of prazosin observed here is similar to the effects reported in other studies examining the role of the α 1 -adrenergic receptor in the locomotor response to amphetamine or cocaine (Arnt 1995;Blanc et al 1994;Darracq et al 1998;Dickinson et al 1988;Drouin et al 2002a;Drouin et al 2002b;Snoddy et al 1985;Wellman et al 2002). In fact, our data indicate that MDMA-induced motor behavior is more sensitive to α 1 -adrenoceptor blockade than that produced by (+)-amphetamine.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this experiment are consistent with the findings of Darracq et al (1998), who had previously reported that prazosin blocked the locomotor stimulant effect of amphetamine. A one-way ANOVA indicated an overall significant effect of prazosin administration on the locomotor response to 2 mg/kg amphetamine (p < 0.01).…”
Section: Effect Of Prazosin On Amphetaminesupporting
confidence: 92%
See 2 more Smart Citations
“…The reduced behavioural response to METH found in alpha1b AR knock out (KO) mice is accompanied by a reduced DA release [122, 123, 129] and absence of DA neurotoxicity [130]. Conversely, transgenic mice overexpressing either wild-type or constitutively active alpha1b ARs show nigrostriatal damage associated with serious locomotor dysfunction, tremor at rest, epileptic seizures, and autonomic dysfunctions [131].…”
Section: The Role Of Ne In Methamphetamine-induced Behavioural Changesmentioning
confidence: 99%